Asthma and rhinitis have different genetic profiles for IL13, IL17A and GSTP1 polymorphisms - Resende, E. P. (2017)
Asthma and rhinitis have a complex etiology, depending on multiple genetic and environmental risk factors. An increasing number of susceptibility genes are currently being identified, but the majority of reported associations have not been consistently replicated across populations of different genetic backgrounds.